2019
DOI: 10.2147/ott.s197338
|View full text |Cite
|
Sign up to set email alerts
|

<p>LINC01296 promotes proliferation, migration, and invasion of HCC cells by targeting miR-122-5P and modulating EMT activity</p>

Abstract: Introduction Long noncoding RNAs (lncRNAs) play an important role in the origination and progression of hepatocellular carcinoma (HCC). However, the biological function of the long intergenic non-protein-coding RNA, LINC01296, in HCC remains unknown. Methods Here, we observed an increase in the expression levels of LINC01296 in HCC tissues and cell lines using reverse transcription quantitative PCR; these data were consistent with that obtained from The Cancer Genome At… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 42 publications
2
11
0
Order By: Relevance
“…Many studies have reported that lncRNAs can interact with miRNA to exert their regulatory functions [12,13]. For example, LINC01296 promotes HCC cells proliferation, migration, and invasion through targeting miR-122-5p [14]. Long noncoding RNA SNHG1 promotes non-small cell lung cancer progression via sponging miR-145-5p [15].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported that lncRNAs can interact with miRNA to exert their regulatory functions [12,13]. For example, LINC01296 promotes HCC cells proliferation, migration, and invasion through targeting miR-122-5p [14]. Long noncoding RNA SNHG1 promotes non-small cell lung cancer progression via sponging miR-145-5p [15].…”
Section: Discussionmentioning
confidence: 99%
“…A total of nine eligible studies21–25 28 31–33 (one gastric cancer, one oesophageal cancer, one prostate cancer, one cholangiocarcinoma, one colon cancer, one breast cancer, one pancreatic ductal adenocarcinoma, one bladder cancer and one hepatocellular carcinoma) were enrolled in this meta-analysis. The basic information and characteristics of each trial were summarised in tables 1–3.…”
Section: Resultsmentioning
confidence: 99%
“…In this meta-analysis, the expression level of LINC01296 was examined by qRT-PCR in all studies. The median expression of LINC01296 in Qin’s,22 Wang’s28 and Wan’s33 articles was regarded as the cut-off value, while the mean expression was set as the cut-off value in Zhang’s,23 Yuan’s25 and Wang’s32 researches. However, other eligible articles did not report the cut-off value.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In colon carcinoma, miR-21a combines with LINC01296 to reverse its carcinogenic effect [12]. In addition, LINC01296/miR-122-5p axis regulate the development of hepatocellular carcinoma through EMT pathway [13]. These findings provided an insight for us to explore how LINC01296 implicated in the progression of OC.…”
Section: Introductionmentioning
confidence: 90%